Changes in sprinting and landing mechanics across 120 minutes of soccer-specific exercise - Field, A.; Fischer, A.; Read, D. B.; Sanderson, A.; Graham-Smith, P.; Birdsey, L.; Harper, L.; Bramah, C.; Page, R. M.; Dos'Santos, T. (The Journal of Strength and Conditioning Research, 2026)
The aim of this study was to examine the influence of 120 minutes of simulated soccer match play on sprinting and landing mechanics. Twelve semiprofessional soccer players completed bilateral vertical drop jumps, countermovement jumps, and 30-m sprints at prematch, half-time, full-time, and post-extra time. Two-dimensional frontal plane footage was captured during jumps, and the frontal plane projection angle upon landing was measured. Sprint-running mechanics were assessed using a novel qualitative screening tool. Drop-jump height reduced 12.5% from prematch (0.32 ± 0.02 m) to extra time (0.28 ± 0.02 m, p = 0.002, d = 0.2), 11.1% from full-time to prematch (0.27 ± 0.02 m; p = 0.013, d = 2.2), and 6.3% from full-time to half-time (0.30 ± 0.02 m; p = 0.001, d = 3.0). Average landing force decreased 4.5% at extra time (1,022.7 ± 38.3 N) vs. prematch (1,068.7 ± 38.5 N; p = 0.003, d = 1.2), 5.5% at half-time (1,078.7 ± 38.3; p = 0.001, d = 0.8), and 3.8% at full-time (1,039.5 ± 38.3) vs. half-time (p = 0.015, d = 0.3). Time to stabilization increased 14.3% at extra time (663 ± 34 ms) from 568 ± 34 ms at prematch (p = 0.009, d = 0.3), 13.7% at half-time (572 ± 34 ms; p = 0.004, d = 0.1), and 9.1% at full-time (663 ± 34; p = 0.011, d = 0.2). Relative peak landing force was 6.9% higher at full-time (692.00 ± 44.44%) vs. half-time (644.79 ± 44.44%; p = 0.009, d = 0.4), but 6.2% lower at half-time vs. prematch (684.50 ± 44.28%; p = 0.022, d = 0.6). Sprint mechanics movement quality deteriorated by 29.5% at half-time (2.75 ± 0.26) compared with prematch (1.95 ± 0.27; p = 0.016, d = 0.5), and by 33.4% from prematch to extra time (2.93 ± 0.27; p = 0.013, d = 0.6). Players may experience impaired neuromuscular performance, particularly during landing and sprinting, which may influence movement quality and could contribute to increased injury susceptibility, although this requires further investigation.